CHEMICAL AND BIOLOGICAL PEST CONTROL OF STORED GRAIN - Бондаренко, И. В. (Scientific Progress & Innovations, 2014)
The results of experimental researches of chemical and biological methods of pest control of grain stocks were presented. During the experiments was determined the technical efficiency of insecticides contact action - Aktellik (pirimiphos-methyl, 0.016 ml/kg), K-Obiol (deltametryn + piperonil butoxide, 0.042 ml/kg, 0.084 ml/kg), biological preparation - Bitoksibatsillin (Bacillus thuringiensis, 3 ml/kg and 6 ml/kg) and their mixtures against pests of grain stocks. The presence of toxic properties in number of herbal preparations: cloves, cumin, vanilla, thyme, mustard, canella, bay leaves, coriander were installed also, determined efficiency of their action in relation to the dominant species of pests of grain stocks.